Electronic conductivity in gadolinium doped ceria under direct current as a trigger for flash sintering. (1st April 2020) - Mishra, Tarini Prasad; Neto, Rubens Roberto Ingraci; Speranza, Giorgio; Quaranta, Alberto; Sglavo, Vincenzo M.; Raj, Rishi; Guillon, Olivier; Bram, Martin; Biesuz, Mattia
Abstract: In this paper, we discuss the progression of flash sintering in 10mol% gadolinium-doped ceria specimens. Flash transition is correlated with the generation of n-type electronic conductivity in air under direct-current bias. Its origin is attributed to partial reduction of the material which propagates from the cathodic-to-anodic region. The phenomenon was observed, in-situ, by monitoring the development of electrochemical blackening during the incubation period of the flash-experiment. Anomalous features, including shift in the valence band edge, shrinkage of the band-gap and change in the oxidation state of Ce in flashed samples was confirmed by X-ray photoelectron spectroscopy and diffuse reflectance measurements. Graphical abstract: Image, graphical abstract